Food and Feeding Habits of Tilapiine Cichlid Fish Oreochromis mossambicus PETERS from Pichavaram Mangrove South East Coast of India - J M A, Prabhu Arachi (International Journal of Pharmaceutical & Biological Archive, 2013)
Food and Feeding Habits of Tilapiine Cichlid Fish Oreochromis mossambicus PETERS from Pichavaram Mangrove South East Coast of India